Les entreprises sociales à la recherche de leur légitimité - Constance Perrin-Joly (Revue Internationale des Études du Développement)
The commitment of social enterprises to Ethiopia’s development is part of a neo-liberal form of government, based on the empowerment of individual actors who are called upon to take part in the common good, thus demonstrating the inability of the state to do so. This has caused tension between social enterprises and the Ethiopian development state, which has a monopoly on development. Social entrepreneurs are perceived as being on the margins of public industrialization policies on the one hand and as promoting an ideological framework that is beyond the government’s control on the other. Ethiopia thus constitutes a privileged observation point of social enterprises’ legitimation strategies as they seek institutional recognition, by resorting to extraversion resources while emphasizing their local roots.